Interaction of foreign-speaking persons with the public services - Morel, Alenka (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2013)
The article presents a pilot study as part of on-going research on community interpreting. It investigates the interaction of foreign-speaking persons with officials in public service administration by exploring the settings, the participants and the characteristics of these situations through empirical survey research. Despite fair language skills, immigrants and officials often encounter difficulties in mutual understanding, whereas an impromptu interpreter may either mistakenly take control over the conversation or empower clients to exercise their rights. Above all, results show that different steps should be taken to enhance successful interlingual interaction and that employing trained interpreters for facilitating communication in the public services should become standard in order to enable equal opportunities for all, regardless of immigrant background.
Keywords: medjezikovno sporazumevanje; tolmačenje za skupnost; Slovenia; Slovenija; komunikacija; priseljenci; javne službe